3D analysis of the technique in elite ski-touring and cross-country skiers engaged in world cup races and on a treadmill - Canclini, A.; Baroni, G.; Pozzo, R.; Pensini, M.; Rossi, G. (Science and Skiing IV, 2008)
INTRODUCTION: In recent years the ski-touring (SKIALP) has acquired more popularity and SKIALP skiers have significantly improved their technical and physiological performances. The complex multiparametric environment conditions (air and snow temperature, track, techniques, gradients, materials, etc.) and the relatively recent development of the discipline, have hindered the performance of specific studies focused on SKIALP main biomechanical Parameters, similar to those performed in cross-country skiing (CCS) (Komi 1987, Smith 1990, Canclini 2000). Being convinced that SKIALP deserves biomechanical investigations, the purpose of our study is to investigate the kinematics of world elite SKIALP skiers on the treadmill and compare SKIALP kinematics patterns with CCS biomechanical parameters (Diagonal Stride-DS) measured during high level competition, simulated races and treadmill.